2021
DOI: 10.1007/s00420-021-01781-0
|View full text |Cite
|
Sign up to set email alerts
|

Causes of irritant contact dermatitis after occupational skin exposure: a systematic review

Abstract: Purpose Irritant contact dermatitis (ICD) is a major cause of occupational disease. The aim was to review the relation between exposure to occupational irritants and ICD and the prognosis of ICD. Methods Through a systematic search, 1516 titles were identified, and 48 studies were included in the systematic review. Results We found that the evidence for an association between ICD and occupational irritants was stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 112 publications
(296 reference statements)
1
19
0
1
Order By: Relevance
“…Wet work is primarily a risk factor for ICD, as water can work as an irritant that easily penetrates into the skin leading to barrier damage. In agreement with the findings of the present review, in a recent systematic review of Jacobsen et al evidence was found for strong association between ICD and wet work exposure 20 …”
Section: Discussionsupporting
confidence: 93%
“…Wet work is primarily a risk factor for ICD, as water can work as an irritant that easily penetrates into the skin leading to barrier damage. In agreement with the findings of the present review, in a recent systematic review of Jacobsen et al evidence was found for strong association between ICD and wet work exposure 20 …”
Section: Discussionsupporting
confidence: 93%
“…ICD usually presents as local dermatitis, which usually precedes ACD, 7 and ICD is usually the main cause of occupational skin disease. 8 The clinical symptoms of the patient we reported were mainly facial burning and tingling, and localized erythematous-edematous and scaly rash. Combining the patient's occupational environment and exposure to irritants, we diagnosed ICD.…”
Section: Discussionmentioning
confidence: 70%
“…ICD usually presents as local dermatitis, which usually precedes ACD, 7 and ICD is usually the main cause of occupational skin disease. 8 …”
Section: Discussionmentioning
confidence: 99%
“…1 The use of liquid-proof gloves is generally recommended in wet-work tasks with the aim of decreasing the frequency of direct contact with water and irritants. 1,2 Glove occlusion is associated with the development of irritant contact dermatitis (ICD), [3][4][5][6] suggesting that occlusion alone might be a major risk factor for the development of ICD. However, according to experimental and field studies, 7,8 only the extensive and prolonged use of gloves, 5 and concomitant exposure to detergents and water seems to be relevant for the occurrence of barrier dysfunction.…”
Section: Introductionmentioning
confidence: 99%